Adverse Neonatal Outcome are More Common among Babies Born by Cesarean Section than Naturally Born Babies at Public Hospitals in Eastern Ethiopia: A Comparative Prospective Follow-Up Study at Eastern Ethiopia - Maleda Tefera; Nega Assefa; Kedir Teji Roba; Letta Gedefa (SAGE Publishing, 2021)
The adverse neonatal outcome is defined as the presence of birth asphyxia, respiratory distress, birth trauma, hypothermia, meconium aspiration syndrome, neonatal intensive care admission, and neonatal death. It is a major concern in developing countries, including Ethiopia. This study tried to identify predictors of adverse neonatal outcomes at selected public hospitals in Eastern Ethiopia. A hospital-based prospective follow-up study was conducted in three public hospitals in Eastern Ethiopia from June to October 2020. A total of 2,246 laboring women and neonates born at the hospitals were enrolled in the study. Data were collected through interviews, observation checklists, and clinical chart review. Reports were presented in relative risks with 95% CIs. The overall magnitude of adverse neonatal outcome was 20.97% (95% CI: 19.33- 22.71%). It was 24.3% for babies born through cesarean section (95% CI: 21.3%, 27.5). The presence of meconium in the amniotic fluid increased the risk for neonates delivered via cesarean section (ARR, 1.52 95% CI; 1.04, 2.22). Among neonates born via vaginal delivery, the risk of adverse neonatal outcome was higher among nullipara women (ARR, 1.42 95% CI; 1.02, 1.99) and among women diagnosed with abnormal labor or pregnancy such as APH, pre-eclampsia, obstructed labor, fetal distress, and mal-presentation at admission (ARR, 1.30 95%CI; 1.01, 1.67). The risk of adverse neonatal outcome was higher among babies born through the cesarian section than those born via vaginal delivery. Abnormal labor or pregnancy and being primiparous increased the risk of adverse neonatal outcome in vaginal delivery.